KUALITAS PELAYANAN PEMBINAAN LEMBAGA PENANGGULANGAN BENCANA TERHADAP KEPUTUSAN SATUAN PENDIDIKAN DALAM MENGGUNAKAN JASA KONSELING PADA MUHAMMADIYAH DISASTER MANAGEMENT CENTER (MDMC) KABUPATEN PAMEKASAN ***) - Surahman Fajar (LP2M IAI Al Khairat Pamekasan, 2020)
Abstract: The context of the problem in this study about “Quality of disastermanagement counseling service for education unit toward decision to usecounseling service of Muhammadiyah Disaster Management Center (MDMC)Pamekasan Regency”. The result of this research by using multiple linearanalyzing show that quality of counseling service for education unit that consistof Reliability X1, Responsiveness X2, Assurance X3, Empaty X4, dan Tangible X5has effect toward decision of education unit in using counseling service ofMuhammadiyah Disaster Management Center (MDMC) Pamekasan Regency. Keywords: Quality of Disaster Management Counseling Service for EducationUnit, Decision to Use Counseling Service of Muhammadiyah DisasterManagement Center (MDMC) Pamekasan Regency